1991
DOI: 10.1210/jcem-72-5-1102
|View full text |Cite
|
Sign up to set email alerts
|

Human Follicular Fluid Contains a Follicle-Stimulating Hormone (FSH) Receptor Binding Inhibitor Which Has FSH Agonist Activity, is Immunologically Similar to FSH, But Can Be Distinguished from FSH*

Abstract: We have previously reported the presence in human follicular fluid (hFF) of a high (greater than 5000) mol wt FSH receptor binding inhibitor (FSH-BI). This hFF FSH-BI was further purified by removal of material insoluble in acidified acetone (pH 4.1) but soluble in diethyl ether (pH 10.5), followed by molecular sieving through Sephacryl S-100. FSH-BI activity eluted from S-100 with an elution volume similar to that of hFSH, but could be distinguished from hFSH on the basis of a differential sensitivity to acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…However, not all FSH-binding inhibitory activity results in inhibition of FSH, because part of these binding inhibitors have FSH agonist activity (22). Results of the present study show that the biological activity of FSH in the context of serum proteins is approximately 50% of the activity in the absence of serum.…”
Section: Discussionmentioning
confidence: 61%
“…However, not all FSH-binding inhibitory activity results in inhibition of FSH, because part of these binding inhibitors have FSH agonist activity (22). Results of the present study show that the biological activity of FSH in the context of serum proteins is approximately 50% of the activity in the absence of serum.…”
Section: Discussionmentioning
confidence: 61%
“…The concentrations (µ /\; mean ± sem) of 17 high-molecular-weight FSHBI was performed using the fraction of UK 10 retentate of large amounts of follicular fluids from medium follicles that was not retained on Blue Sepharose CL6B. Figure 3 shows anion-exchange FPLC of the fraction not retained on Blue Sepharese CL6B and FSHBI activity of the eluates.…”
Section: Resultsmentioning
confidence: 99%
“…Sluss et al. Lee et al (17,18) have reported the presence of high-molecular-weight (M 5 7 000) FSHBI in human follicular fluids. Lee et al (17,18) have reported the presence of high-molecular-weight (M 5 7 000) FSHBI in human follicular fluids.…”
mentioning
confidence: 99%
“…Analysis of binding kinetics can give results that are different for intact and deglycosylated FSH (212). These assays may also be affected by FSH-like molecules (213) or other inhibitory materials (214). The physiological basis of such molecules remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%